Urban development of the coastal system of the Italian largest islands: Sicily and Sardinia. (1st July 2017) - Fiorini, L.; Zullo, F.; Romano, B.
Abstract: The phenomenon of urban sprawl has already been recognized as one of the major anthropic threats to natural ecosystems. This study investigates the spatial distribution of urban expansion with reference to two Italian Islands, Sicily and Sardinia, from post-war to the first decade of the 2000s (i.e. noughties). The two Regions are an important tourist destination in the Mediterranean basin, owing to their landscapes and climate. The analysis produced a series of interesting results, such as the average annual speed of transformation of the coastal strip or the size and modalities of urban development, correlated with demographic and morphological parameters. The study also focused on the urban transformations that have affected the protected areas within these Regions. The final part of the work is fully devoted to the policies and techniques that should be adopted in the remaining coastal stretches, that is those not yet affected by urban transformation. In fact, for these areas policies should be focused on the preservation of community habitats and the protection of ecological connections with relevant consequences in the national biodiversity conservation. With regards to the processed data allowed to draw a map of management responsibilities at municipal and regional levels for the review of future urban planning in terms of sustainable governance. Highlights: Investigation of urban transformations for Sicily and Sardinia, in the last 50 years. Focus on the urban transformations that have affected the coastal system. Regional urban evolution and comparison with altitude belts and protected areas.